Development of a Basic Learning Module on Unit Conversion and Energy Based on Science Literacy - , (Universitas Muhammadiyah Enrekang, 2026)
This study aims to develop a science literacy-based learning module on unit conversion and energy and to analyze its feasibility and students’ responses. The research employed a Research and Development (R&D) method using the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The participants were 45 tenth-grade students of senior high school (SMA/MA). Data were collected through expert validation sheets and student response questionnaires. The results indicated that the developed module achieved a feasibility score of 80.78%, categorized as feasible, covering aspects of content, language, presentation, and scientific literacy. Furthermore, students’ responses showed an average score of 99.17%, categorized as very good. The module was found to improve students’ conceptual understanding, analytical skills, and ability to apply concepts in real-life contexts. Therefore, the science literacy-based learning module is considered both feasible and effective as instructional material for science learning at the senior high school level.